Neuroimmune System as a Driving Force for Plasticity Following CNS Injury - O’Reilly, Micaela L.; Tom, Veronica J. (Frontiers in Cellular Neuroscience, 2020)
Following an injury to the central nervous system (CNS), spontaneous plasticity is observed throughout the neuraxis and affects multiple key circuits. Much of this spontaneous plasticity can elicit beneficial and deleterious functional outcomes, depending on the context of plasticity and circuit affected. Injury-induced activation of the neuroimmune system has been proposed to be a major factor in driving this plasticity, as neuroimmune and inflammatory factors have been shown to influence cellular, synaptic, structural, and anatomical plasticity. Here, we will review the mechanisms through which the neuroimmune system mediates plasticity after CNS injury. Understanding the role of specific neuroimmune factors in driving adaptive and maladaptive plasticity may offer valuable therapeutic insight into how to promote adaptive plasticity and/or diminish maladaptive plasticity, respectively.